Cardiovascular imagingTo uncover what is unknown or forgotten – cardiac magnetic resonance in the identification of vascular pathologies in patients after tetralogy of Fallot repair - Śpiewak, Mateusz; A. Małek, Łukasz; Biernacka, Elżbieta K.; Kowalski, Mirosław; Hoffman, Piotr; Demkow, Marcin; Miśko, Jolanta; Rużyłło, Witold; Marczak, Magdalena (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : In patients with repaired tetralogy of Fallot (TOF), various pathologies of the vascular system (both arterial and venous) may be present as a result of the previous therapeutic procedures or due to the congenital disease itself. Because of the limited diagnostic capabilities in the past, lacking surgical reports of patients operated on several decades ago and/or a long time since a corrective procedure, some of these pathologies/anomalies may remain unknown. Aim : To identify selected vascular pathologies with the use of cardiac magnetic resonance in patients after TOF repair. Material and methods: We included 208 consecutive patients (median age 24.9 years, interquartile range 20.5–36.7; 126 (60.6%) males) with repaired TOF undergoing cardiac magnetic resonance (CMR) imaging. Results : Significant unexpected vascular pathologies/anomalies were found in 30 patients (14.4%) and included: uni- or bilateral occlusion of the subclavian artery (n = 20), persistent left superior vena cava (n = 7, in 1 case draining into the left atrium), occluded subclavian vein (n = 1), and interruption of the inferior vena cava (n = 2). Additionally, 1 patient with the left subclavian artery occluded had an occlusion of the brachiocephalic vein. In none of the patients was the information about the uncovered pathology/anomaly present either in the referral information or in the present medical history. Conclusions : The CMR in patients with repaired TOF may uncover some pathologies/anomalies which were unknown or forgotten at the time of patients’ referral for the study, and which may have a significant impact on patient management.